The effect of habitat loss and fragmentation on isolation by distance and divergence - Gabriele Maria Sgarlata; Tiago Maié; Tiago de Zoeten; Jordi Salmona; Rita Rasteiro; Lounès Chikhi (Proceedings of the National Academy of Sciences, 2025)
Natural habitats have undergone drastic changes in quality, continuity, and extent during the Pleistocene, influencing the distribution of many species. More recently, human activities have converted continuous habitats into fragmented and isolated patches. Recent meta-analyses suggest that habitat loss and fragmentation (HL&F) have negatively impacted the genetic diversity of species but very few studies have analyzed the consequences of HL&F on the spatial distribution of genetic diversity and on isolation by distance (IBD) patterns (i.e., correlations between genetic and geographical distances) observed in many species. In this work, we use spatial simulations to investigate the speed at which IBD patterns generated in continuous habitats are lost in a context of HL&F. We characterized the behavior of IBD in the case of i) instantaneous HL&F, ii) gradual (two-steps) HL&F, and iii) range expansion followed by instantaneous HL&F. In addition, we show that a spatially explicit theoretical framework based on previous IBD theoretical results can be modified and applied to a toroidal stepping-stone model undergoing HL&F. Our results suggest that IBD patterns can be maintained for long periods of time after HL&F, thus pointing to the long-term persistence of signatures associated to past habitat connectivity in the genetic diversity of many species, even if they went through major and sometimes ancient fragmentation events. This suggests that some present-day fragmented species, who still exhibit significant IBD patterns, may have been partly disconnected for very long periods, on the order of tens of thousands of years for species with long generation time.